Portraits and philosophy - Maes, Hans, 1975- (Routledge research in aesthetics., 2020)
"Portraiture is one of the most well-established genres in art. One finds portraits not just in museums and galleries, but also in newspapers and magazines, in the homes of people and in the boardrooms of companies, on stamps and coins, and on millions of cell phones and computers. Despite its huge popularity, however, portraiture hasn't received much philosophical attention. While there are countless art historical studies of portraiture, including self-portraiture and group-portraiture, contemporary philosophy has largely remained silent on the subject. This book brings together philosophers and philosophically minded art historians with different areas of expertise to discuss this enduring and continuously fascinating genre. The essays in this volume are grouped into thematic sections, each of which is guided by numerous research questions relevant to the genre of portraiture. Part I explores the boundaries of portraiture. What makes something a portrait? In what way is it similar to and different from other genres? How have artists pushed the limits and conventions of the portraiture? How does the recent vogue of selfies relate to the tradition of self-portraiture? Part II responds to questions about empathy and emotion in portraiture. How do artists express attitudes and emotions towards sitters of their portraits? Why are we moved by certain portraits and not so much by others? In Part III, the contributors address questions about fiction and depiction. Do portraits fall within the domain of non-fiction? Can authenticity in portraiture be achieved if portraits necessarily involve posing? Finally, Part IV grapples with the following question: What are the moral dimensions of the relation between artist, sitter, patron, and audience? Portraits and Philosophy tangles with deep questions about the nature and effects of portraiture in ways that will substantially advance the scholarly discussion of the genre. It will be of interest to scholars and students working in philosophy of art, history of art, and the visual arts"--